Global citizenship and the challenge from cultural relativism - Thomas Hylland Eriksen (University of Belgrade, 2017)
Do human beings live in a shared world or in several? The traditional answer from social and cultural anthropology has been that although the physical world is uniform, the world as it is perceived by humans is fundamentally and irreducibly diverse, since human worlds are culturally constructed and cultures are unique and particular in character.